2019
DOI: 10.1103/physrevb.100.125123
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced localization and protection of topological edge states due to geometric frustration

Abstract: Topologically non-trivial phases are linked to the appearance of localized modes in the boundaries of an open insulator. On the other hand, the existence of geometric frustration gives rise to degenerate localized bulk states. The interplay of these two phenomena may, in principle, result in an enhanced protection/localization of edge states. In this paper, we study a two-dimensional Lieb-based topological insulator with staggered hopping parameters and diagonal open boundary conditions. This system belongs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Similar behavior to that of the extended SSH chain should be present in other bipartite 1D [26,[29][30][31] and 2D [32][33][34][35] topological insulators if long-range hopping terms are introduced. A simple 2D example where the approach of this paper can be applied is that of a plane of parallel extended SSH chains with uniform or staggered hopping terms between them.…”
Section: Discussionsupporting
confidence: 55%
“…Similar behavior to that of the extended SSH chain should be present in other bipartite 1D [26,[29][30][31] and 2D [32][33][34][35] topological insulators if long-range hopping terms are introduced. A simple 2D example where the approach of this paper can be applied is that of a plane of parallel extended SSH chains with uniform or staggered hopping terms between them.…”
Section: Discussionsupporting
confidence: 55%
“…Note, here, we do not attempt to load into the BLT states, meaning we loose population into the other states that overlap with the initial state. For experimental scenarios, it would be prudent to instead use state preparation schemes or shortcuts to adiabaticity to load efficiently into the BLT states [88][89][90].…”
Section: Bulk Localised Transportmentioning
confidence: 99%
“…We illustrated in Ref. [19] by considering periodic boundary conditions in the y-direction, that these geometrically enhanced edge states exist at the ak y = π point in the Brillouin zone.…”
Section: Geometrically Protected Edge Statesmentioning
confidence: 99%
“…Also, in Ref. [19] we showed that for non-interacting particles, these edge states can be prepared by an adiabatic ramping protocol, where we simulated a time- dependent variation of the value of the tunnelling dimerisation J 1 /J 2 . In Fig.…”
Section: Geometrically Protected Edge Statesmentioning
confidence: 99%
See 1 more Smart Citation